2018
DOI: 10.1038/s41418-017-0040-0
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian endoreplication emerges to reveal a potential developmental timer

Abstract: Among the most intriguing and relevant questions in physiology is how developing tissues correctly coordinate proliferation with differentiation. Endoreplication, in a broad sense, is a consequence of a cell division block in the presence of an active cell cycle, and it typically occurs as cells differentiate terminally to fulfill a specialised function. Until recently, endoreplication was thought to be a rare variation of the cell cycle in mammals, more common in invertebrates and plants. However, in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 59 publications
2
47
0
Order By: Relevance
“…The protective cells that cover the skin, keratinocytes, undergo endomitosis and endocycling to a maximum ploidy of 12C (Gandarillas and Freije, 2014). Polyploidization of keratinocytes is induced by UV irradiation and is likely to increase tolerance to genotoxic stress (Gandarillas, 2012;Gandarillas et al, 2018), as reported in hepatocytes (Zhang et al, 2018). In fact, in plants, strains with increased ploidy are more resistant to UV radiation (Gegas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The protective cells that cover the skin, keratinocytes, undergo endomitosis and endocycling to a maximum ploidy of 12C (Gandarillas and Freije, 2014). Polyploidization of keratinocytes is induced by UV irradiation and is likely to increase tolerance to genotoxic stress (Gandarillas, 2012;Gandarillas et al, 2018), as reported in hepatocytes (Zhang et al, 2018). In fact, in plants, strains with increased ploidy are more resistant to UV radiation (Gegas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Plant epidermal or Drosophila epithelial cells are well known for becoming large due to endoreplication. Similarly, in human an increasing variety of cell types are currently known to become large by endoreplication [10]. For instance, suprabasal keratinocytes enlarge as they differentiate [34,51], megakaryocytes fragment into platelets after polyploidysation [52], and mammary milk producing cells became large and binucleated [53].…”
Section: Discussionmentioning
confidence: 99%
“…These cells slip from the mitotic checkpoints and enter a new round of DNA replication. As other cell types, keratinocytes can also slip from a G2 arrest, undergoing mitotis bypass [10,11]. A differentiation-mitosis checkpoint (DMC) would be highly instrumental in developing tissues where apoptosis would be deleterious.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mitotic slippage occurs when cdk1 is prematurely inactivated during a G2/M arrest 43 , 44 . In addition, in various systems mitotic slippage has been proposed to protect cells from apoptosis (refs in Gandarillas et al 45 ). Although p53 is part of the G2 checkpoint to promote DNA repair, the lack of p53, by not allowing full repair, provokes a G2/M arrest 12 .…”
Section: Discussionmentioning
confidence: 99%